2012
DOI: 10.1111/j.1559-1816.2012.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mentoring Relationship as a Context for Psychological Contract Development

Abstract: This study examined the mentoring relationship as a context for the development of psychological contracts and investigated the obligations that mentors and protégés feel that they owe and are owed in the mentoring relationship. By using psychological contract theory, we develop new insights into the dynamics of the mentoring relationship and extend psychological contract research by applying the theory to a relation outside the employer-employee context. Results indicate that both parties perceive that they o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 66 publications
(101 reference statements)
1
29
0
Order By: Relevance
“…As such, the findings are consistent with past mentoring researchers who have noted that the mentoring relationship was key to a mentee's growth and professional fulfillment and satisfaction (Allen & Eby, 2004;Barker, 2006;Haggard & Turban, 2012;Strayhorn & Saddler, 2009). Often times, counselor education mentors move between various roles when working with students and other faculty mentees.…”
Section: Discussionsupporting
confidence: 79%
“…As such, the findings are consistent with past mentoring researchers who have noted that the mentoring relationship was key to a mentee's growth and professional fulfillment and satisfaction (Allen & Eby, 2004;Barker, 2006;Haggard & Turban, 2012;Strayhorn & Saddler, 2009). Often times, counselor education mentors move between various roles when working with students and other faculty mentees.…”
Section: Discussionsupporting
confidence: 79%
“…Nurse educator protégés and mentors also identified open communication and availability as important qualities of a mentor (Huybrecht et al, 2011; White et al, 2010; Wilson et al, 2010). Haggard and Turban (2012) identified mentors’ availability to talk with protégés as a relational obligation of the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This difference highlights the vulnerability of protégés and their desire for a safe environment where mentors can listen without criticism. Ehrich et al (2004) reported that mentors who were “critical” resulted in problematic protégé outcomes. Haggard and Turban (2012) identified acceptance as a relational obligation of the mentor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krishnan, 2011;O'Donohue, Donohue, & Grimmer, 2007;Rousseau & Schalk, 2000); Raeder, Knorr, & Hilb, 2012;Thomas et al, 2010) and within a variety of distinct contexts (e.g. Haggard & Turban, 2012;McDermott, Heffernan, & Beynon, 2013;Sparrow, 1996).…”
Section: Psychological Contractsmentioning
confidence: 99%